ANALISIS JALUR KRITIS PADA PENJADWALAN PROYEK PEMBANGUNAN ATAP UTILITY HUB E-COMMERCE BOGOR DENGAN METODE CPM DAN PERT - Fahrezi, Moch Agung; Kusmanto, Kusmanto; Sutrisno, Sutrisno (BAROMETER, 2023)
This study discusses the project completion time in the construction of a utility located in the Bogor E-Commerce Hub warehouse using the CPM and PERT methods. In addition, the critical path in the sequence of project activities will also be identified using a Network Diagram. At the end of the discussion of this study, the probability or probability of completing this project is calculated and how big is the probability or possibility if this project is accelerated or slowed down. There are 13 sequences of activities in this project with a total time of 105 days and the activities that require the longest time are finishing activities which take 29 days and the shortest activity is 1 day. From the critical path analysis using the Network Diagram, it was found that all activities in this project are critical activities that cannot be postponed and must be carried out immediately after the previous activity has been completed. In the calculation using the CPM method, the results of the project completion are 105 days, while for the PERT calculation the results are 104.5 days. The probability of this project's completion time being accelerated to 104 days is 40.90%.